Attenuation of SARS-CoV-2 replication and associated inflammation by concomitant targeting of viral and host cap 2'-O-ribose methyltransferases - Bergant, Valter; Yamada, Shintaro; Grass, Vincent; Tsukamoto, Yuta; Lavacca, Teresa; Krey, Karsten; Muhlhofer, Maria-Teresa; Wittmann, Sabine; Enßer, Armin; Herrmann, Alexandra; Vom Hemdt, Anja; Tomita, Yuriko; et al. (EMBO Journal, 2022)
The SARS-CoV-2 infection cycle is a multistage process that relies on functional interactions between the host and the pathogen. Here, we repurposed antiviral drugs against both viral and host enzymes to pharmaceutically block methylation of the viral RNA 2'-O-ribose cap needed for viral immune escape. We find that the host cap 2'-O-ribose methyltransferase MTr1 can compensate for loss of viral NSP16 methyltransferase in facilitating virus replication. Concomitant inhibition of MTr1 and NSP16 efficiently suppresses SARS-CoV-2 replication. Using in silico target-based drug screening, we identify a bispecific MTr1/NSP16 inhibitor with anti-SARS-CoV-2 activity in vitro and in vivo but with unfavorable side effects. We further show antiviral activity of inhibitors that target independent stages of the host SAM cycle providing the methyltransferase co-substrate. In particular, the adenosylhomocysteinase (AHCY) inhibitor DZNep is antiviral in in vitro, in ex vivo, and in a mouse infection model and synergizes with existing COVID-19 treatments. Moreover, DZNep exhibits a strong immunomodulatory effect curbing infection-induced hyperinflammation and reduces lung fibrosis markers ex vivo. Thus, multispecific and metabolic MTase inhibitors constitute yet unexplored treatment options against COVID-19.
CRIS-Team WoS Importer:2022-08-05

A viral kinase counteracts in vivo restriction of murine cytomegalovirus by SAMHD1 - Deutschmann, Janina; Schneider, Andrea; Gruska, Iris; Vetter, Barbara; Thomas, Dominique; Kießling, Melissa; Wittmann, Sabine; Herrmann, Alexandra; Schindler, Michael; Milbradt, Jens; Ferreirós, Nerea; Winkler, Thomas; et al. (Nature Microbiology, 2019)
The deoxynucleotide triphosphate (dNTP) hydrolase SAMHD1 inhibits retroviruses in non-dividing myeloid cells. Although antiviral activity towards DNA viruses has also been demonstrated, the role of SAMHD1 during cytomegalovirus (CMV) infection remains unclear. To determine the impact of SAMHD1 on the replication of CMV, we used murine CMV (MCMV) to infect a previously established SAMHD1 knockout mouse model and found that SAMHD1 inhibits the replication of MCMV in vivo. By comparing the replication of MCMV in vitro in myeloid cells and fibroblasts from SAMHD1-knockout and control mice, we found that the viral kinase M97 counteracts SAMHD1 after infection by phosphorylating the regulatory residue threonine 603. The phosphorylation of SAMHD1 in infected cells correlated with a reduced level of dNTP hydrolase activity and the loss of viral restriction. Together, we demonstrate that SAMHD1 acts as a restriction factor in vivo and we identify the M97-mediated phosphorylation of SAMHD1 as a previously undescribed viral countermeasure.
CRIS-Team Scopus Importer:2019-11-01

Cytoplasmic HIV-RNA in monocytes determines microglial activation and neuronal cell death in HIV-associated neurodegeneration - Faissner, Simon; Ambrosius, Bjoern; Schanzmann, Kirsten; Grewe, Bastian; Potthoff, Anja; Muench, Jan; Sure, Ulrich; Gramberg, Thomas; Wittmann, Sabine; Brockmeyer, Norbert; Ueberla, Klaus; Gold, Ralf; et al. (Experimental Neurology, 2014)
Despite highly active antiretroviral therapy, HIV-associated neurocognitive disorders (HAND) are still highly prevalent. Direct neurotoxicity of microglia activated by HIV-infected monocytes independent from viral replication may account for this observation. To investigate underlying molecular and viral determinants, human monocytoid cells (U937) transduced with HIV-particles were co-cultured with primary human microglia or astrocytes. Using genetically-engineered HIV-particles key steps of infection were examined. Levels of pro-inflammatory/neurotoxic cytokines were investigated in co-culture supernatants by flow cytometry. Neurotoxicity mediated by the supernatants was analysed using primary cortical rat neurons. To corroborate our findings, cytokine profiles in cerebrospinal fluid (CSF) of neuropsychologically asymptomatic HIV positive (HIV(+)) patients (n=45) were correlated with neurofilament H (NfH) as surrogate of neuronal/axonal degeneration. In contrast to direct exposure of HIV to microglia, only the presence of HIV-transduced monocytoid cells strongly activated human microglia as evidenced by enhanced secretion of CXCL10, CCL5, CCL2, and IL-6 (1.3-7.1-fold; p<0.01) leading to two-fold increased neurotoxicity (p<0.001). In direct comparison, astrocyte activation by HIV-transduced monocytoid cells was limited. Using different mutant HIV-particles we show that the presence of cytoplasmic HIV-RNA in monocytoid cells is the viral determinant for this unique microglial activation pattern and subsequent neuronal cell death; reverse transcription and expression of viral genes were not essential. In CSF of presymptomatic HIV(+) patients, CXCL10, CCL5 and IL-6 were correlated with NfH as surrogate marker of neurodegeneration as well as CSF-pleocytosis. In conclusion, cytosolic viral RNA in monocytes is mandatory for subsequent microglial activation and neurotoxicity; activated astrocytes may augment neuroinflammation. In addition, neuroinflammation and neurodegeneration occur even in preclinical HIV(+) patients and are associated with cytokines regulated in vitro. Our data may aid in the development of biomarkers and glia-directed therapeutic approaches of HAND.
EVALuna2:8227

Deficiency for SAMHD1 activates MDA5 in a cGAS/STING-dependent manner - Schumann, Tina; Ramon, Santiago Costas; Schubert, Nadja; Mayo, Mohamad Aref; Hega, Melanie; Maser, Katharina Isabell; Ada, Servi Remzi; Sydow, Lukas; Hajikazemi, Mona; Badstübner, Markus; Müller, Patrick; Ge, Yan; et al. (Journal of Experimental Medicine, 2023)
Defects in nucleic acid metabolizing enzymes can lead to spontaneous but selective activation of either cGAS/STING or RIG-like receptor (RLR) signaling, causing type I interferon-driven inflammatory diseases. In these pathophysiological conditions, activation of the DNA sensor cGAS and IFN production are linked to spontaneous DNA damage. Physiological, or tonic, IFN signaling on the other hand is essential to functionally prime nucleic acid sensing pathways. Here, we show that low-level chronic DNA damage in mice lacking the Aicardi-Goutières syndrome gene SAMHD1 reduced tumor-free survival when crossed to a p53-deficient, but not to a DNA mismatch repair-deficient background. Increased DNA damage did not result in higher levels of type I interferon. Instead, we found that the chronic interferon response in SAMHD1-deficient mice was driven by the MDA5/MAVS pathway but required functional priming through the cGAS/STING pathway. Our work positions cGAS/STING upstream of tonic IFN signaling in Samhd1-deficient mice and highlights an important role of the pathway in physiological and pathophysiological innate immune priming.
CRIS-Team Scopus Importer:2022-11-25

Editorial: Strategies to Defeat HIV - Serra-Moreno, Ruth; Gramberg, Thomas (Current HIV Research, 2016)
EVALuna2:8303

Human cytomegalovirus overcomes SAMHD1 restriction in macrophages via pUL97 - Businger, Ramona; Deutschmann, Janina; Gruska, Iris; Milbradt, Jens; Wiebusch, Lüder; Gramberg, Thomas; Schindler, Michael (Nature Microbiology, 2019)
The host restriction factor sterile alpha motif and histidine–aspartate domain-containing protein 1 (SAMHD1) is an important component of the innate immune system. By regulating the intracellular nucleotide pool, SAMHD1 influences cell division and restricts the replication of viruses that depend on high nucleotide concentrations. Human cytomegalovirus (HCMV) is a pathogenic virus with a tropism for non-dividing myeloid cells, in which SAMHD1 is catalytically active. Here we investigate how HCMV achieves efficient propagation in these cells despite the SAMHD1-mediated dNTP depletion. Our analysis reveals that SAMHD1 has the capability to suppress HCMV replication. However, HCMV has evolved potent countermeasures to circumvent this block. HCMV interferes with SAMHD1 steady-state expression and actively induces SAMHD1 phosphorylation using the viral kinase pUL97 and by hijacking cellular kinases. These actions convert SAMHD1 to its inactive phosphorylated form. This mechanism of SAMHD1 inactivation by phosphorylation might also be used by other viruses to overcome intrinsic immunity.
CRIS-Team Scopus Importer:2019-11-01

Human TRIM5 alpha senses and restricts LINE-1 elements - Volkmann, Bianca; Wittmann, Sabine; Lagisquet, Justine; Deutschmann, Janina; Eißmann, Kristin; Ross, James J.; Biesinger, Brigitte; Gramberg, Thomas (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Mobile genetic elements have significantly shaped our genomic landscape. LINE-1 retroelements are the only autonomously active elements left in the human genome. Since new insertions can have detrimental consequences, cells need to efficiently control LINE-1 retrotransposition. Here, we demonstrate that the intrinsic immune factor TRIM5 alpha senses and restricts LINE-1 retroelements. Previously, rhesus TRIM5 alpha has been shown to efficiently block HIV-1 replication, while human TRIM5 alpha was found to be less active. Surprisingly, we found that both human and rhesus TRIM5 alpha efficiently repress human LINE-1 retrotransposition. TRIM5 alpha interacts with LINE-1 ribonucleoprotein complexes in the cytoplasm, which is essential for restriction. In line with its postulated role as pattern recognition receptor, we show that TRIM5 alpha also induces innate immune signaling upon interaction with LINE-1 ribonucleoprotein complexes. The signaling events activate the transcription factors AP-1 and NF-kappa B, leading to the down-regulation of LINE-1 promoter activity. Together, our findings identify LINE-1 as important target of human TRIM5 alpha, which restricts and senses LINE-1 via two distinct mechanisms. Our results corroborate TRIM5 alpha as pattern recognition receptor and shed light on its previously undescribed activity against mobile genetic elements, such as LINE-1, to protect the integrity of our genome.
CRIS-Team WoS Importer:2020-08-21

IFI16 Targets the Transcription Factor Sp1 to Suppress HIV-1 Transcription and Latency Reactivation - Hotter, Dominik; Bosso, Matteo; Jønsson, Kasper L.; Krapp, Christian; Stürzel, Christina M.; Das, Atze; Littwitz-Salomon, Elisabeth; Berkhout, Ben; Russ, Alina; Wittmann, Sabine; Gramberg, Thomas; Zheng, Yue; et al. (Cell Host & Microbe, 2019)
The interferon γ-inducible protein 16 (IFI16) is known as immune sensor of retroviral DNA intermediates. We show that IFI16 restricts HIV-1 independently of immune sensing by binding and inhibiting the host transcription factor Sp1 that drives viral gene expression. This antiretroviral activity and ability to bind Sp1 require the N-terminal pyrin domain and nuclear localization of IFI16, but not the HIN domains involved in DNA binding. Highly prevalent clade C HIV-1 strains are more resistant to IFI16 and less dependent on Sp1 than other HIV-1 subtypes. Furthermore, inhibition of Sp1 by IFI16 or pharmacologically by Mithramycin A suppresses reactivation of latent HIV-1 in CD4+ T cells. Finally, IFI16 also inhibits retrotransposition of LINE-1, known to engage Sp1, and murine IFI16 homologs restrict Friend retrovirus replication in mice. Thus, IFI16 restricts retroviruses and retrotransposons by interfering with Sp1-dependent gene expression, and evasion from this restriction may facilitate spread of HIV-1 subtype C.
CRIS-Team Scopus Importer:2019-06-18
Keywords: HIV-1; interferon γ-inducible PYHIN protein 16; PYHIN proteins; restriction factors; Sp1 transcription factor

Interactions of LSECtin and DC-SIGN/DC-SIGNR with viral ligands: Differential pH dependence, internalization and virion binding - Gramberg, Thomas; Soilleux, Elizabeth; Fisch, Tanja; Lalor, Patricia F.; Hofmann, Heike; Wheeldon, Sophie; Cotterill, Andrew; Wegele, Anja; Winkler, Thomas; Adams, David H.; Poehlmann, Stefan (Virology, 2008)
The calcium-dependent lectins DC-SIGN and DC-SIGNR (collectively termed DC-SIGN/R) bind to high-mannose carbohydrates on a variety of viruses. In contrast, the related lectin LSECtin does not recognize mannose-rich glycans and interacts with a more restricted spectrum of viruses. Here, we analyzed whether these lectins differ in their mode of ligand engagement. LSECtin and DC-SIGNR, which we found to be co-expressed by liver, lymph node and bone marrow sinusoidal endothelial cells, bound to soluble Ebola virus glycoprotein (EBOV-GP) with comparable affinities. Similarly, LSECtin, DC-SIGN and the Langerhans cell-specific lectin Langerin readily bound to soluble human immunodeficiency virus type-1 (HIV-1) GP. However, only DC-SIGN captured HIV-1 particles, indicating that binding to soluble GP is not necessarily predictive of binding to virion-associatedGP. Capture of EBOV-GP by LSECtin triggered ligand internalization, suggesting that LSECtin like DC-SIGN might function as an antigen uptake receptor. However, the intracellular fate of lectin-ligand complexes might differ. Thus, exposure to low-pH medium, which mimics the acidic luminal environment in endosomes/lysosomes, released ligand bound to DC-SIGN/R but had no effect on LSECtin interactions with ligand. Our results reveal important differences between pathogen capture by DC-SIGN/R and LSECtin and hint towards different biological functions of these lectins. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: LSECtin; DC-SIGN; HIV; attachment; lectin; Ebola

Mouse SAMHD1 has antiretroviral activity and suppresses a spontaneous cell-intrinsic antiviral response - Behrendt, Rayk; Schumann, Tina; Gerbaulet, Alexander; Nguyen, Laura A.; Schubert, Nadja; Alexopoulou, Dimitra; Berka, Ursula; Lienenklaus, Stefan; Peschke, Katrin; Gibbert, Kathrin; Wittmann, Sabine; Lindemann, Dirk; et al. (Cell Reports, 2013)
Aicardi-Goutières syndrome (AGS), a hereditary autoimmune disease, clinically and biochemically overlaps with systemic lupus erythematosus (SLE) and, like SLE, is characterized by spontaneous type I interferon (IFN) production. The finding that defects of intracellular nucleases cause AGS led to the concept that intracellular accumulation of nucleic acids triggers inappropriate production of type I IFN and autoimmunity. AGS can also be caused bydefects of SAMHD1, a 3@ exonuclease and deoxynucleotide (dNTP) triphosphohydrolase. Human SAMHD1 is an HIV-1 restriction factor that hydrolyzes dNTPs and decreases their concentrationbelow the levels required for retroviral reverse transcription. We show in gene-targeted mice that also mouse SAMHD1 reduces cellular dNTP concentrations and restricts retroviral replication in lymphocytes, macrophages, and dendritic cells. Importantly, the absence of SAMHD1 triggered IFN-β-dependent transcriptional upregulation of type I IFN-inducible genes in various cell types indicative of spontaneous IFN production. SAMHD1-deficient mice may be instrumental for elucidating the mechanisms that trigger pathogenic type I IFN responses in AGS and SLE
CRIS-Team Scopus Importer:2024-07-25

Nsp16 shields SARS–CoV-2 from efficient MDA5 sensing and IFIT1-mediated restriction - Ruß, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Enßer, Armin; Kato, Hiroki; Gramberg, Thomas (EMBO Reports, 2022)
Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′-O-methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV-2 harboring a catalytically inactive 2′-O-methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV-2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′-O-methyltransferase Nsp16 during SARS–CoV-2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon-induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV-2 strains and as a potential candidate for therapeutic intervention.
CRIS-Team Scopus Importer:2022-11-04
Keywords: 2′-O-methyltransferase; IFIT1; MDA5; Nsp16; SARS–CoV-2

Nuclear PYHIN proteins target the host transcription factor Sp1 thereby restricting HIV-1 in human macrophages and CD4+ T cells - Bosso, Matteo; Prelli Bozzo, Caterina; Hotter, Dominik; Volcic, Meta; Stürzel, Christina M.; Rammelt, Annika; Ni, Yi; Urban, Stephan; Becker, Miriam; Schelhaas, Mario; Wittmann, Sabine; Christensen, Maria H.; et al. (PLoS Pathogens, 2020)
Members of the family of pyrin and HIN domain containing (PYHIN) proteins play an emerging role in innate immunity. While absent in melanoma 2 (AIM2) acts a cytosolic sensor of non-self DNA and plays a key role in inflammasome assembly, the γ-interferon-inducible protein 16 (IFI16) restricts retroviral gene expression by sequestering the transcription factor Sp1. Here, we show that the remaining two human PYHIN proteins, i.e. myeloid cell nuclear differentiation antigen (MNDA) and pyrin and HIN domain family member 1 (PYHIN1 or IFIX) share this antiretroviral function of IFI16. On average, knock-down of each of these three nuclear PYHIN proteins increased infectious HIV-1 yield from human macrophages by more than an order of magnitude. Similarly, knock-down of IFI16 strongly increased virus transcription and production in primary CD4+ T cells. The N-terminal pyrin domain (PYD) plus linker region containing a nuclear localization signal (NLS) were generally required and sufficient for Sp1 sequestration and anti-HIV-1 activity of IFI16, MNDA and PYHIN1. Replacement of the linker region of AIM2 by the NLS-containing linker of IFI16 resulted in a predominantly nuclear localization and conferred direct antiviral activity to AIM2 while attenuating its ability to form inflammasomes. The reverse change caused nuclear-to-cytoplasmic relocalization of IFI16 and impaired its antiretroviral activity but did not result in inflammasome assembly. We further show that the Zn-finger domain of Sp1 is critical for the interaction with IFI16 supporting that pyrin domains compete with DNA for Sp1 binding. Finally, we found that human PYHIN proteins also inhibit Hepatitis B virus and simian vacuolating virus 40 as well as the LINE-1 retrotransposon. Altogether, our data show that IFI16, PYHIN1 and MNDA restrict HIV-1 and other viral pathogens by interfering with Sp1-dependent gene expression and support an important role of nuclear PYHIN proteins in innate antiviral immunity.
CRIS-Team Scopus Importer:2020-08-28

Phosphorylation of murine SAMHD1 regulates its antiretroviral activity - Wittmann, Sabine; Behrendt, Rayk; Eißmann, Kristin; Volkmann, Bianca; Thomas, Dominique; Ebert, Thomas; Cribier, Alexandra; Benkirane, Monsef; Hornung, Veit; Bouzas, Nerea Ferreiros; Gramberg, Thomas (Retrovirology, 2015)
Human SAMHD1 is a triphosphohydrolase that restricts the replication of retroviruses, retroelements and DNA viruses in noncycling cells. While modes of action have been extensively described for human SAMHD1, only little is known about the regulation of SAMHD1 in the mouse. Here, we characterize the antiviral activity of murine SAMHD1 with the help of knockout mice to shed light on the regulation and the mechanism of the SAMHD1 restriction and to validate the SAMHD1 knockout mouse model for the use in future infectivity studies.We found that endogenous mouse SAMHD1 restricts not only HIV-1 but also MLV reporter virus infection at the level of reverse transcription in primary myeloid cells. Similar to the human protein, the antiviral activity of murine SAMHD1 is regulated through phosphorylation at threonine 603 and is limited to nondividing cells. Comparing the susceptibility to infection with intracellular dNTP levels and SAMHD1 phosphorylation in different cell types shows that both functions are important determinants of the antiviral activity of murine SAMHD1. In contrast, we found the proposed RNase activity of SAMHD1 to be less important and could not detect any effect of mouse or human SAMHD1 on the level of incoming viral RNA.Our findings show that SAMHD1 in the mouse blocks retroviral infection at the level of reverse transcription and is regulated through cell cycle-dependent phosphorylation. We show that the antiviral restriction mediated by murine SAMHD1 is mechanistically similar to what is known for the human protein, making the SAMHD1 knockout mouse model a valuable tool to characterize the influence of SAMHD1 on the replication of different viruses in vivo.
EVALuna2:8275

Recognize Yourself-Innate Sensing of Non-LTR Retrotransposons - Lagisquet, Justine; Zuber, Kilian; Gramberg, Thomas (Viruses, 2021)
Although mobile genetic elements, or transposons, have played an important role in genome evolution, excess activity of mobile elements can have detrimental consequences. Already, the enhanced expression of transposons-derived nucleic acids can trigger autoimmune reactions that may result in severe autoinflammatory disorders. Thus, cells contain several layers of protective measures to restrict transposons and to sense the enhanced activity of these "intragenomic pathogens". This review focuses on our current understanding of immunogenic patterns derived from the most active elements in humans, the retrotransposons long interspersed element (LINE)-1 and Alu. We describe the role of known pattern recognition receptors in nucleic acid sensing of LINE-1 and Alu and the possible consequences for autoimmune diseases.
CRIS-Team WoS Importer:2021-02-12

SAMHD1 … and Viral Ways around It. - Deutschmann, Janina; Gramberg, Thomas (Viruses, 2021)
The SAM and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase that plays a crucial role for a variety of different cellular functions. Besides balancing intracellular dNTP concentrations, facilitating DNA damage repair, and dampening excessive immune responses, SAMHD1 has been shown to act as a major restriction factor against various virus species. In addition to its well-described activity against retroviruses such as HIV-1, SAMHD1 has been identified to reduce the infectivity of different DNA viruses such as the herpesviruses CMV and EBV, the poxvirus VACV, or the hepadnavirus HBV. While some viruses are efficiently restricted by SAMHD1, others have developed evasion mechanisms that antagonize the antiviral activity of SAMHD1. Within this review, we summarize the different cellular functions of SAMHD1 and highlight the countermeasures viruses have evolved to neutralize the restriction factor SAMHD1.
CRIS-Team WoS Importer:2021-04-09

SAMHD1 in Retroviral Restriction and Innate Immune Sensing–Should We Leash the Hound? - Herrmann, Alexandra; Happel, Anna-Ursula; Gramberg, Thomas (Current HIV Research, 2016)
The antiviral restriction factor SAM domain and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase and thereby contributes to the regulation of intracellular dNTP levels. SAMHD1 blocks retroviral infection at the level of reverse transcription in myeloid cells and resting CD4+ T cells and is counteracted by the accessory protein Vpx, which is encoded by human immunodeficiency virus 2 (HIV-2) and several simian immunodeficiency virus (SIV) strains. Recently, it has been shown that the antiviral activity of SAMHD1 in myeloid dendritic cells (DC) hampers the induction of an efficient immune response directed against HIV-1.Within this review, we will summarize recent advances on the biology of SAMHD1 and its function as an antiviral restriction factor. In addition, we will discuss its role in autoimmunity and the antiviral immune response directed against HIV-1 and will evaluate the possibility of modulating SAMHD1 activity to generate an enhanced antiretroviral immune response.
EVALuna2:8304

SAMHD1 restricts HIV-1 infection in resting CD4 + T cells - Baldauf, Hanna Mari; Pan, Xiaoyu; Erikson, Elina; Schmidt, Sarah; Daddacha, Waaqo; Burggraf, Manja; Schenkova, Kristina; Ambiel, Ina; Wabnitz, Guido; Gramberg, Thomas; Panitz, Sylvia; Flory, Egbert; et al. (Nature Medicine, 2012)
Unlike activated CD4 + T cells, resting CD4 + T cells are highly resistant to productive HIV-1 infection. Early after HIV-1 entry, a major block limits reverse transcription of incoming viral genomes. Here we show that the deoxynucleoside triphosphate triphosphohydrolase SAMHD1 prevents reverse transcription of HIV-1 RNA in resting CD4 + T cells. SAMHD1 is abundantly expressed in resting CD4 + T cells circulating in peripheral blood and residing in lymphoid organs. The early restriction to infection in unstimulated CD4 + T cells is overcome by HIV-1 or HIV-2 virions into which viral Vpx is artificially or naturally packaged, respectively, or by addition of exogenous deoxynucleosides. Vpx-mediated proteasomal degradation of SAMHD1 and elevation of intracellular deoxynucleotide pools precede successful infection by Vpx-carrying HIV. Resting CD4 + T cells from healthy donors following SAMHD1 silencing or from a patient with Aicardi-Goutières syndrome homozygous for a nonsense mutation in SAMHD1 were permissive for HIV-1 infection. Thus, SAMHD1 imposes an effective restriction to HIV-1 infection in the large pool of noncycling CD4 + T cells in vivo. Bypassing SAMHD1 was insufficient for the release of viral progeny, implicating other barriers at later stages of HIV replication. Together, these findings may unveil new ways to interfere with the immune evasion and T cell immunopathology of pandemic HIV-1. © 2012 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2024-07-25

SAMHD1 restricts the replication of human immunodeficiency virus type 1 by depleting the intracellular pool of deoxynucleoside triphosphates - Lahouassa, Hichem; Daddacha, Waaqo; Hofmann, Henning; Ayinde, Diana; Logue, Eric C.; Dragin, Loïc; Bloch, Nicolin; Maudet, Claire; Bertrand, Matthieu; Gramberg, Thomas; Pancino, Gianfranco; Priet, Stéphane; et al. (Nature Immunology, 2012)
SAMHD1 restricts the infection of dendritic and other myeloid cells by human immunodeficiency virus type 1 (HIV-1), but in lentiviruses of the simian immunodeficiency virus of sooty mangabey (SIVsm)-HIV-2 lineage, SAMHD1 is counteracted by the virion-packaged accessory protein Vpx. Here we found that SAMHD1 restricted infection by hydrolyzing intracellular deoxynucleoside triphosphates (dNTPs), lowering their concentrations to below those required for the synthesis of the viral DNA by reverse transcriptase (RT). SAMHD1-mediated restriction was alleviated by the addition of exogenous deoxynucleosides. An HIV-1 with a mutant RT with low affinity for dNTPs was particularly sensitive to SAMHD1-mediated restriction. Vpx prevented the SAMHD1-mediated decrease in dNTP concentration and induced the degradation of human and rhesus macaque SAMHD1 but had no effect on mouse SAMHD1. Nucleotide-pool depletion could be a general mechanism for protecting cells from infectious agents that replicate through a DNA intermediate. © 2012 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2024-07-25

Sequence-specific activation of the DNA sensor cGAS by Y-form DNA structures as found in primary HIV-1 cDNA - Herzner, Anna-Maria; Hagmann, Cristina Amparo; Goldeck, Marion; Wolter, Steven; Kuebler, Kirsten; Wittmann, Sabine; Gramberg, Thomas; Andreeva, Liudmila; Hopfner, Karl-Peter; Mertens, Christina; Zillinger, Thomas; Jin, Tengchuan; et al. (Nature Immunology, 2015)
Cytosolic DNA that emerges during infection with a retrovirus or DNA virus triggers antiviral type I interferon responses. So far, only double-stranded DNA (dsDNA) over 40 base pairs (bp) in length has been considered immunostimulatory. Here we found that unpaired DNA nucleotides flanking short base-paired DNA stretches, as in stem-loop structures of single-stranded DNA (ssDNA) derived from human immunodeficiency virus type 1 (HIV-1), activated the type I interferon-inducing DNA sensor cGAS in a sequence-dependent manner. DNA structures containing unpaired guanosines flanking short (12- to 20-bp) dsDNA (Y-form DNA) were highly stimulatory and specifically enhanced the enzymatic activity of cGAS. Furthermore, we found that primary HIV-1 reverse transcripts represented the predominant viral cytosolic DNA species during early infection of macrophages and that these ssDNAs were highly immunostimulatory. Collectively, our study identifies unpaired guanosines in Y-form DNA as a highly active, minimal cGAS recognition motif that enables detection of HIV-1 ssDNA.
EVALuna2:8285

Spontaneous Type I IFN response in SAMHD1-deficient mice requires both, functional intracellular RNA and DNA sensing pathways - Behrendt, R.; Schumann, T.; Gerbaulet, A.; Wittmann, Sabine; Gramberg, Thomas; Roers, A. (Pediatric Rheumatology, 2015)
CRIS-Team Scopus Importer:2024-07-25

Strategies to defeat HIV - Serra-Moreno, Ruth; Gramberg, Thomas (Current HIV Research, 2016)
CRIS-Team Scopus Importer:2024-07-25

The SAMHD1-mediated block of LINE-1 retroelements is regulated by phosphorylation - Herrmann, Alexandra; Wittmann, Sabine; Thomas, Dominique; Shepard, Caitlin N.; Kim, Baek; Ferreiros, Nerea; Gramberg, Thomas (Mobile DNA, 2018)
Background: The restriction factor SAMHD1 regulates intracellular nucleotide level by degrading dNTPs and blocks the replication of retroviruses and DNA viruses in non-cycling cells, like macrophages or dendritic cells. In patients, inactivating mutations in samhd1 are associated with the autoimmune disease Aicardi-Goutieres Syndrome (AGS). The accumulation of intracellular nucleic acids derived from endogenous retroelements thriving in the absence of SAMHD1 has been discussed as potential trigger of the autoimmune reaction. In vitro, SAMHD1 has been found to restrict endogenous retroelements, like LINE-1 elements (L1). The mechanism, however, by which SAMHD1 blocks endogenous retroelements, is still unclear. Results: Here, we show that SAMHD1 inhibits the replication of L1 and other endogenous retroelements in cycling cells. By applying GFP- and neomycin-based reporter assays we found that the anti-L1 activity of SAMHD1 is regulated by phosphorylation at threonine 592 (T592). Similar to the block of HIV, the cofactor binding site and the enzymatic active HD domain of SAMHD1 proofed to be essential for restriction of L1 elements. However, phosphorylation at T592 did not correlate with the dNTP hydrolase activity of SAMHD1 in cycling 293T cells suggesting an alternative mechanism of regulation. Interestingly, we found that SAMHD1 binds to ORF2 protein of L1 and that this interaction is regulated by T592 phosphorylation. Together with the finding that the block is also active in cycling cells, our results suggest that the SAMHD1-mediated inhibition of L1 is similar but not identical to HIV restriction. Conclusion: Our findings show conclusively that SAMHD1 restricts the replication of endogenous retroelements in vitro. The results suggest that SAMHD1 is important for maintaining genome integrity and support the idea of an enhanced replication of endogenous retroelements in the absence of SAMHD1 in vivo, potentially triggering autoimmune diseases like AGS. Our analysis also contributes to the better understanding of the activities of SAMHD1 in antiviral defense and nucleotide metabolism. The finding that the phosphorylation of SAMHD1 at T592 regulates its activity against retroelements but not necessarily intracellular dNTP level suggests that the dNTP hydrolase activity might not be the only function of SAMHD1 important for its antiviral activity and for controlling autoimmunity.
EVALuna2:35283

Transmembrane Serine Protease 2 and Proteolytic Activation of the Epithelial Sodium Channel in Mouse Kidney - Sure, Florian; Afonso, Sara; Essigke, Daniel; Schmidt, Paul; Kalo, M. Zaher; Nesterov, Viatcheslav; Kißler, Alicia; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Broeker, Katharina A.E.; Gramberg, Thomas; et al. (Journal of the American Society of Nephrology, 2024)
Background The renal epithelial sodium channel (ENaC) is essential for sodium balance and blood pressure control. ENaC undergoes complex proteolytic activation by not yet clearly identified tubular proteases. Here, we examined a potential role of transmembrane serine protease 2 (TMPRSS2). Methods Murine ENaC and TMPRSS2 were (co-)expressed in Xenopus laevis oocytes. ENaC cleavage and function were studied in TMPRSS2-deficient murine cortical collecting duct (mCCDcl1) cells and TMPRSS2-knockout (Tmprss2−/−) mice. Short-circuit currents (ISC) were measured to assess ENaC-mediated transepithelial sodium transport of mCCDcl1 cells. The mCCDcl1 cell transcriptome was studied using RNA sequencing. The effect of low-sodium diet with or without high potassium were compared in Tmprss2−/− and wildtype mice using metabolic cages. ENaC-mediated whole-cell currents were recorded from microdissected tubules of Tmprss2−/− and wildtype mice. Results In oocytes, co-expression of murine TMPRSS2 and ENaC resulted in fully cleaved γ-ENaC and 2-fold stimulation of ENaC currents. High baseline expression of TMPRSS2 was detected in mCCDcl1 cells without a stimulatory effect of aldosterone on its function or transcription. TMPRSS2 knockout in mCCDcl1 cells compromised γ-ENaC cleavage and reduced baseline and aldosterone-stimulated ISC which could be rescued by chymotrypsin. A compensatory transcriptional upregulation of other proteases was not observed. Tmprss2−/− mice kept on standard diet exhibited no apparent phenotype, but renal γ-ENaC cleavage was altered. In response to a low-salt diet, particularly with high potassium intake, Tmprss2−/− mice increased plasma aldosterone significantly more than wildtype mice to achieve a similar reduction of renal sodium excretion. Importantly, the stimulatory effect of trypsin on renal tubular ENaC currents was much more pronounced in Tmprss2−/− mice than that in wildtype mice. This indicated the presence of incompletely cleaved and less active channels at the cell surface of TMPRSS2-deficient tubular epithelial cells. Conclusions TMPRSS2 contributes to proteolytic ENaC activation in mouse kidney in vivo.
CRIS-Team Scopus Importer:2024-11-08

Transmembrane serine protease 2 (TMPRSS2) is involved in proteolytic activation of the epithelial sodium channel (ENaC) in mouse cortical collecting duct (mCCDcl1) cells - Sure, Florian; Afonso, Sara; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Gramberg, Thomas; Ilyaskin, Alexandr; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, A.; Rinke, Ralf; Madej, M. G.; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, Alexei; Rinke, Ralf; Madej, M. Gregor; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2022)
The epithelial sodium channel (ENaC) is a heterotrimer consisting of alpha-, beta-, and gamma-subunits. Channel activation requires proteolytic release of inhibitory tracts from the extracellular domains of alpha-ENaC and gamma-ENaC; however, the proteases involved in the removal of the gamma-inhibitory tract remain unclear. In several epithelial tissues, ENaC is coexpressed with the transmembrane serine protease 2 (TMPRSS2). Here, we explored the effect of human TMPRSS2 on human alpha beta gamma-ENaC heterologously expressed in Xenopus laevis oocytes. We found that coexpression of TMPRSS2 stimulated ENaC-mediated whole-cell currents by approximately threefold, likely because of an increase in average channel open probability. Furthermore, TMPRSS2-dependent ENaC stimulation was not observed using a catalytically inactive TMPRSS2 mutant and was associated with fully cleaved gamma-ENaC in the intracellular and cell surface protein fractions. This stimulatory effect of TMPRSS2 on ENaC was partially preserved when inhibiting its proteolytic activity at the cell surface using aprotinin but was abolished when the gamma-inhibitory tract remained attached to its binding site following introduction of two cysteine residues (S155C-Q426C) to form a disulfide bridge. In addition, computer simulations and site-directed mutagenesis experiments indicated that TMPRSS2 can cleave gamma-ENaC at sites both proximal and distal to the gamma-inhibitory tract. This suggests a dual role of TMPRSS2 in the proteolytic release of the gamma-inhibitory tract. Finally, we demonstrated that TMPRSS2 knockdown in cultured human airway epithelial cells (H441) reduced baseline proteolytic activation of endogenously expressed ENaC. Thus, we conclude that TMPRSS2 is likely to contribute to proteolytic ENaC activation in epithelial tissues in vivo.
CRIS-Team WoS Importer:2022-06-24

TRIM19/PML Restricts HIV Infection in a Cell Type-Dependent Manner - Kahle, Tanja; Volkmann, Bianca; Eißmann, Kristin; Herrmann, Alexandra; Schmitt, Sven; Wittmann, Sabine; Merkel, Laura; Reuter, Nina; Stamminger, Thomas; Gramberg, Thomas (Viruses, 2016)
The promyelocytic leukemia protein (PML) is the main structural component of the nuclear matrix structures termed nuclear domain 10 (ND10) or PML nuclear bodies (PML-NBs). PML and ND10 structures have been shown to mediate an intrinsic immune response against a variety of different viruses. Their role during retroviral replication, however, is still controversially discussed. In this study, we analyzed the role of PML and the ND10 components Daxx and Sp100 during retroviral replication in different cell types. Using cell lines exhibiting a shRNA-mediated knockdown, we found that PML, but not Daxx or Sp100, inhibits HIV and other retroviruses in a cell type-dependent manner. The PML-mediated block to retroviral infection was active in primary human fibroblasts and murine embryonic fibroblasts but absent from T cells and myeloid cell lines. Quantitative PCR analysis of HIV cDNA in infected cells revealed that PML restricts infection at the level of reverse transcription. Our findings shed light on the controversial role of PML during retroviral infection and show that PML contributes to the intrinsic restriction of retroviral infections in a cell type-dependent manner.
EVALuna2:8305